Analisis Pelaksanaan Kewenangan Camat Dalam Perencanaan Pembangunan Di Kecamatan Bangko Pusako Kabupaten Rokan Hilir - Nur, Rahmat; Monalisa, Monalisa (UIR PRESS, 2015)
Rokan Hilir in the decree No. 28 of 2012 on devolution Most Authority Regents To Subdistrict, explained that there are a number of required and elective matters delegated by the regent To camat among which Affairs Development Planning. For the sub-district should be in the position of facilitating and accommodate the needs and sensitivity as a measure of the problem and what the needs of the community in implementing development. The purpose of this study was to determine how the exercise of authority in the sub-district development planning in the District Bangko Pusako Rokan Hilir. The theory used in this research is the theory of development planning by Sjafrizal. This study uses quantitative methods to type a descriptive survey research. The sampling technique for the representation of delegates village and community using purposive sampling method will choose informen research deemed to know the information and the problem in depth and can be trusted as a source of data. The collection of data obtained directly from respondents through interviews, questionnaires and observation. To analyze the data using the tools of the frequency table and the results will be concluded. Based on the research that has been done can be concluded that the implementation of the Authority Subdistrict In Development Planning in Sub Bangko Pusako can Rokan Hilir Done Enough said. Suggestions given to the District Government by a district head in order to actually run the policy that has been given for the sake of encouraging faster development process in order to realize an advanced society, and prosperous.